The determinants of Capital Structure of Chinese listed firms: Do overcapacity firms have the same capital structure? - Feng, Manyu (2016)
This study investigates the determinants of capital structure for Chinese listed firms by employing the fixed effect model in the period of 2005-2015. Compared with the previous studies, overcapacity problem is considered in this study thus data sets are divided in to three groups by different capital utilization. The aim of this paper is to investigate the factors may affect capital choice decision of firms which has overcapacity problems. In order to explain the relationship between determinants and leverage, some theories like agency theory, pecking order theory, and trade-off theory are applied in this study. Through comparing the difference of determinants of capital structure in each group, the independent variables that are related with leverage for overcapacity firms are significantly different from non-overcapacity firms and overall Chinese listed firms. As the regression result shown, profit, size, tangibility, non-debt tax shield and ownership structure are significant related with leverage for firms, which have overcapacity problems.